Wireless sensor network security - López, Javier; Zhou, Jianying (Cryptology and information security series, 2008)
Wireless sensor networks (WSN) is especially vulnerable against external and internal attacks due to its particular characteristics. This book provides an overview of the major security issues that various WSN designers have to face, and also gives a comprehensive guide of solutions and open problems.